2002
DOI: 10.1002/ar.10064
|View full text |Cite
|
Sign up to set email alerts
|

Cell kinetic study of the endometrium by nonisotopic in situ hybridization for histone H3 messenger RNA and immunohistochemistry for Ki‐67 and for estrogen and progesterone receptors

Abstract: We investigated the cell kinetics of the endometrium in hysterectomy specimens taken for leiomyoma from 22 women with regular ovulatory menstrual cycles. Formalin-fixed, paraffin-embedded tissue sections were examined for proliferating activity using histone H3 messenger RNA in situ hybridization (H3 mRNA-ISH) and immunostaining for the Ki-67 antigen. The relationship of the proliferative activity of endometrial cells to the immunohistochemical expression of the estrogen receptor (ER) and the progesterone rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…In a normal menstrual cycle maximum Ki-67 expression in the endometrial cells is seen in the follicular phase which decreases by half during the early luteal phase and virtually ceases during the mid-and late-luteal phase. 18,19 Besides the premenstrual endometrium, the ER, PR and Ki-67 status have also been described in the post menopausal, hyperplastic and neoplastic endometria. 20 However, their levels in inflammatory lesions of endometrium have not been studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…In a normal menstrual cycle maximum Ki-67 expression in the endometrial cells is seen in the follicular phase which decreases by half during the early luteal phase and virtually ceases during the mid-and late-luteal phase. 18,19 Besides the premenstrual endometrium, the ER, PR and Ki-67 status have also been described in the post menopausal, hyperplastic and neoplastic endometria. 20 However, their levels in inflammatory lesions of endometrium have not been studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, we found that Ki 67 expression was significantly higher in carcinomas than adenomas, and a Ki 67 LI ≥14.55 was found to be an indicator of malignancy for pediatric adrenocortical neoplasms. The assessment of cells in the S phase of the cell cycle is an alternative method for evaluating proliferating cells [2,5,10]. In situ hybridization of histone H3 and/or H4 mRNA is an assay used to detect S-phase cells in archival paraffin-embedded material [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…During the S phase of the cell cycle, the level of histone mRNA increases over 50-fold and rapidly disappears at the start of G 2 . The rapid degradation of the histone mRNA after the S phase provides an opportunity to distinguish the proliferating cells in S phase by in situ hybridization for histone mRNA [2,10,15]. Rauttiainen et al reported that nonisotopic histone mRNA in situ hybridization is a reproducible method for measuring the proliferative activity of tumor cells and an independent prognostic factor in astrocytomas [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since H3 mRNA-ISH did not label SMCs in the LP, they are very stable cells, H3 mRNA-ISH being the most reliable method for the detection of S-phase cells in ordinary paraffin sections (Hayama et al 2002;Maeyama et al 1997). There is no information available concerning what kind of factors might control the proliferation and structure of these SMCs.…”
Section: Discussionmentioning
confidence: 99%